Exploring the "Liminal" and "Sacred" Associated with Death in Hinduism through the Hindu Brahminic Death Rituals - Tripathi, Khyati (Open theology, 2022)
This article aims to present the specificities associated with the Hindu liminal phase and the sacred associated with death through an ethnographic account of the death rituals of the Hindu Saryuparin Brahmin community. Through this ethnographic account, the author argues against a uniform liminal phase across different cultures by bringing to the fore aspects specific to the Hindu liminal phase in death. This aids in analyzing the Hindu cosmogenic world and the movement of the deceased’s "pret" or "ghost" within the same during the liminal phase. Building a connect between the liminal and the sacred in Hinduism, the author further discusses how the sacred is understood in terms of purity/impurity and life/death through death rituals. While exploring the sacred, the author contests the classical understanding of the sacred within the religious realm and presents its contextual nature by discussing the "context-based sacred." This article is divided into three sections: (1) death rituals in the Hindu Brahminic tradition, (2) deconstructing the "liminal" in death in Hinduism, and (3) understanding the "sacred" associated with death in Hinduism.